Impact of lockdowns on critical care service demand in a metropolitan hospital in Melbourne, Australia. (8th August 2021) - Tan, Sing Chee; Cross, Anthony; Ghosh, Angajendra
Abstract: Objective: There is a growing recognition of the impact of lockdowns on non‐COVID‐19 demand for critical care services. While a reduction in demand has been postulated, there remains a paucity of quantitative data on the extent and nature of this reduction. The present study aims to quantify the impact of lockdown on critical care services, namely ED, intensive care unit (ICU), medical emergency team (MET) and emergency theatre (ET) demand, during the lockdown in Victoria, Australia. Methods: This is a single‐centred, retrospective observational study on critical service demand, comparing activity levels during the lockdown (31 March to 27 October 2020) with the matched time period from 1 year prior. Results: There was a reduction in presentations to ED (27.2%), MET calls (27.4%), ICU patient episodes (14.5%) and ET bookings (5.8%). There was an unexpected increase in ICU admissions for metabolic diagnoses, comprising drug overdoses and diabetic ketoacidosis, and a reduction in respiratory ICU admissions. There was a reduction across all ED triage categories, which included triage 1 and 2 patients, indicating a reduction even in life‐threatening and emergency presentations. Conclusion: Lockdowns lead to a significant reduction in ICU, MET call and ED demand, and to a lesser extent ET demand. This pattern should be considered in surge capacity and workforce redeployment planning. There are also impacts on public health epidemiology, with potential adverse consequences on mental health and chronic disease management. Further research on the impact of lockdowns on long‐term disease outcomes is needed. Abstract : Lockdowns are associated with an overall reduction in critical care service demand, although this was less pronounced in emergency theatre demand. There was a disproportionate increase in ICU admissions for drug overdoses and diabetic crises, suggest adverse impacts on mental health and chronic disease management.